Economic freedom at metropolitan statistical area borders. Issue 2 (19th January 2023) - Murphy, Ryan H.; Taylor, Ellen; Stansel, Dean
Abstract: This paper applies a variation on differences‐in‐differences to the effects of economic freedom in matched bordering metropolitan statistical areas using the Metropolitan Economic Freedom Index. While a great deal of research has explored the relationship between economic freedom and economic performance, less has been done at the local level. We find that economic freedom has a positive effect on several measures of economic performance, but no effect on population.